Pengawasan Rehabilitasi Saluran Air Jalan Cimedang Kota Blitar - Yurnalisdel, Yurnalisdel; Pandulu, Galih Damar; Sa'dillah, M.; Wijaya, Handika Setya; Ningrum, Diana (Universitas Tribhuwana Tunggadewi Malang, 2025)
An effective strategy to improve the drainage system on Cimedang Street by integrating local expertise and resources can reduce the negative impacts of rainwater accumulation. A collaborative approach from local government, universities, and communities is actively involved in building effective drainage solutions in Bendo Village. The targeted community service activity is supervising the rehabilitation of the Cimedang Street drainage channel. The supervision results illustrate that the implementation of the Cimedang Street Drainage Channel Rehabilitation is ahead of schedule, which is completed in the seventh week with a cumulative realization of 100% of the cumulative planned weight of 42.33%. Testing of materials such as concrete and aggregates shows results that meet technical specifications and test results with concrete compressive strength of 3 samples with a compressive force of 495.9-530.4 KN with a cylinder compressive strength of 28.06-30.01 MPa. This activity results in an adequate acceleration of time realization of 57.67% and concrete compressive strength test results of20 MPa.ABSTRAKStrategi yang efektif dalam peningkatan sistem saluran air di jalan Cimedang melalui penggabungan keahlian dan sumber daya lokal dapat mengurangi dampak buruk dari akumulasi air hujan. Pendekatan kolaboratif dari pemerintah daerah, perguruan tinggi dan masyarakat yang secara aktif terlibat untuk membangun solusi saluran air yang efektif di kelurahan Bendo. Kegiatan pelayanan masyarakat yang ditargetkan adalah pengawasan rehabilitasi saluran air jalan Cimedang. Hasil pengawasan menggambarkan pelaksanaan Rehabilitasi Saluran Air Jl. Cimedang lebih cepat dari jadwal yaitu selesai pada minggu ke 7 dengan kumulatif relisasi bobot 100% dari Komulatif bobot rencana sebesar 42,33%. Pengujian material seperti beton dan agregat menunjukkan hasil yang memenuhi spesifikasi teknis dan hasil uji dengan kekuatan tekan beton 3 sampel dengan gaya tekan 495,9-530,4 KN dengan kuat tekan silinder 28,06-30,01 Mpa. Kegiatan ini menghasilkan efektifitas percepatan realisasi waktu sebesar 57,67% dan hasil uji kuat tekan beton yang 20 Mpa.